2018
DOI: 10.14710/jitaa.43.1.9-18
|View full text |Cite
|
Sign up to set email alerts
|

Morphometrics and genetic diversity of Tegal, Magelang and their crossbred ducks based on Cytochrome b gene

Abstract: This experiment was conducted to study the morphometric and genetic diversity of Tegal, Magelang, and their crossbred ducks. Each ten female about twenty weeks old ducks from Tegal, Magelang, Gallang, and Maggal ducks, respectively, were used as the group materialss. The body weight, chest circumference, body length, shank length, neck length, and pubis width were recorded and tested by analysis of variance of one way classification as the morphometric characteristics. Polymorphism of cytochrome b (cyt b) gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
1
4
0
5
Order By: Relevance
“…All of the previous studies reported that the black phenotype in domestic ducks is caused by a gain-of-function mutation in the extended black (E) locus which harbored by the MC1R gene.All of the morphometric traits of this study varied significantly among the genotypes except shank and wing length in both males and females. Similar to our findings,Henrik et al (2018) reported that reciprocal crosses increased the morphometric measurements in Indonesian local duck populations.…”
supporting
confidence: 92%
“…All of the previous studies reported that the black phenotype in domestic ducks is caused by a gain-of-function mutation in the extended black (E) locus which harbored by the MC1R gene.All of the morphometric traits of this study varied significantly among the genotypes except shank and wing length in both males and females. Similar to our findings,Henrik et al (2018) reported that reciprocal crosses increased the morphometric measurements in Indonesian local duck populations.…”
supporting
confidence: 92%
“…It forms their characteristics which can be passed on to subsequent offspring. Genetic and morphometric diversity are important for breeding management and increasing productivity of these local ducks (Henrik, Purwantini and Ismoyowati, 2018), design of animal breeding programs, genetic mapping, and molecular markers (Yakubu, Kaankuka and Ugbo, 2011;Rusdin et al, 2020). One of the local duck genetic resources possessed by the Riau Islands Province is Sawang duck (Setioko, Prasetyo and Sinurat.…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu, itik Sikumbang Jonti betina memiliki panjang leher terpanjang dibandingkan itik Pitalah dan itik (Maharani et al 2019). Selain itu, itik Sikumbang Jonti memiliki bobot badan yang lebih rendah dari itik Magelang (Henrik, Purwantini, and Ismoyowati, 2018) dan itik Alabio (Suryana et al 2014), tetapi lebih tinggi dari itik Tegal. Itik Sikumbang Jonti memiliki ukuran lebar pelvis yang lebih kecil dibandingkan itik Magelang dan itik Tegal (Henrik, Purwantini, and Ismoyowati, 2018).…”
unclassified